A Study Of Entrepreneurial Characteristics And Entrepreneurial Intention Among Electrical and Electronic Engineering Students - Azizan, Anim Zalina; Lim, Chi Chuan (Research in Management of Technology and Business, 2023)
Entrepreneurship is flourishing all over the world. It promotes the economic growth and development of a country. It is important for job creation, innovation and growth. Therefore, it is the engine that drives the national economy. Regarding the unemployment problem among graduates, policy-makers and academicians have raised serious concerns. The first objective was to identify the entrepreneurial characteristics among electrical and electronic engineering students. The second objective was determining entrepreneurial intention among electrical and electronic engineering students. The third objective of the study was to identify the relationship between entrepreneurial characteristics and entrepreneurial intention among the electrical and electronic engineering students at UTHM. The scope of this study is limited to electrical and electronic engineering students at UTHM. This study uses the quantitative research method of questionnaire to collect data, and the data sources include primary and secondary data. Descriptive analysis and correlation analysis are used for this study to analyze the collected data. The key finding of this research is that entrepreneurial characteristics have a significant positive relationship with entrepreneurial intention. However, the scope of this research is limited, so the suggestion for future research is to expand the scope research.